Modeling of chlorine decay in drinking water supply systems using EPANET MSX - Monteiro, L. (2014)
The modelling of chlorine residual in water supply systems is of great importance in managing disinfectant concentrations throughout the network. First order decay kinetics are currently often used to describe both bulk and wall chlorine consumption. However, more complex approaches have been proposed, namely a parallel, two-reactant second order decay model (2R model) that has been reported as yielding better accuracy for simulating chlorine bulk decay in laboratory tests. The recent EPANET Multi-Species Extension (EPANET MSX) brought enhanced capabilities for the simulation of chlorine residuals in water supply systems, including the use of the 2R model or any other formulation. In the current paper, the performance of the 2R model as well as of first and nth order decay kinetics was assessed for full scale modelling of chlorine in a transmission system. Results have shown that a similar level of accuracy can be achieved with the three tested kinetic models, provided that a good calibration of the wall decay coefficient is accomplished. Although with improved modelling capabilities, the use of the stand- alone EPANET MSX was less user-friendly than normal EPANET application by the lack of a graphical interface allowing for the visualization of chlorine concentration profiles along the system. The use of the 3D-enabled Epanet Java web application circumvented such limitations. This tool together with a better characterization and estimation of the bulk and wall decay components allow for a more practical and accurate modelling of chlorine in water supply systems, while taking advantage of EPANET MSX's enhanced capabilities.